Decentralization and Regional Economic Growth in Indonesia: An Analysis of Governance and Fiscal Decentralization - Roberts Maharjan (Institute for Law and Economics Studies, 2024)
This research paper examines the factors that drive regional economic growth in Indonesia's era of decentralization. Drawing on a mixed-methods approach, the study combines quantitative analysis of secondary data with qualitative insights from interviews and focus groups. The research aims to provide a comprehensive analysis of the factors influencing regional economic growth and to inform policy-making efforts aimed at promoting inclusive and sustainable development across all regions of Indonesia. The findings suggest that governance, fiscal decentralization, natural resource management, infrastructure, and human capital development are critical drivers of regional economic growth. Decentralization has empowered local governments to make decisions that are more responsive to the needs of their constituents, leading to improvements in service delivery and overall economic development. Fiscal decentralization has enabled regions to mobilize resources and invest in infrastructure and human capital, contributing to higher levels of economic growth.